Nuevos registros de distribución de Cerambycidae (Coleoptera) para Chiapas/New distributional records of Cerambycidae (Coleoptera) from Chiapas - Chamé Vázquez, Eduardo Rafael; Sánchez-Hernández, Gibrán (Instituto de Ecología, A.C., 2015)
Five new distributional records are presented. Birandra (Yvesandra) angulicollis (Bates 1879), Parandra (Tavandra) polita Say 1835, Derobrachus procerus Thomson 1860, Chlorida festiva (Linnaeus 1758) and Carneades grandis (Thomson 1860) are reported for the first time from Chiapas.